2019
DOI: 10.5565/rev/isogloss.60
|View full text |Cite
|
Sign up to set email alerts
|

The microvariation of the Spanish perfect in three varieties

Abstract: This study investigates the variability in the use of the Preterit canté ('I sang') and the Present Perfect he cantado ('I have sung') across three Spanish dialects: Peninsular (PEN), Peruvian (PER) and Argentinian (AR). For this purpose, we analyze the effect of type of context and temporal adverbials on the selection of these two forms. The corpus has been obtained through online questionnaires, comprising a total of thirty-two exercises that evaluate the use of the two verb forms in the following contexts: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…De Jonge ( 2001), for his part, has found that in Argentina the Present Perfect highlights a situation within a narration and is used to refer to remote events and, according to Howe (2006), this form is used to refer to both recent and remote events in Perú. González, Jara Yupanqui and Kleinherenbrink (2019) also shown in a study that examines three different Spanish varieties (Peninsular, Peruvian and Argentinian Spanish) that for native speakers of European Spanish and Latin American Spanish the past tense forms are preferred differently in multiple contexts illustrated in a binary contextualized questionnaire. There were, indeed, significant differences in the uses of the studied past tense forms among the three varieties, which strengthens the idea that there is no linguistic consistency within the different Spanish varieties.…”
Section: Language Variation In Tense and Aspectmentioning
confidence: 94%
See 2 more Smart Citations
“…De Jonge ( 2001), for his part, has found that in Argentina the Present Perfect highlights a situation within a narration and is used to refer to remote events and, according to Howe (2006), this form is used to refer to both recent and remote events in Perú. González, Jara Yupanqui and Kleinherenbrink (2019) also shown in a study that examines three different Spanish varieties (Peninsular, Peruvian and Argentinian Spanish) that for native speakers of European Spanish and Latin American Spanish the past tense forms are preferred differently in multiple contexts illustrated in a binary contextualized questionnaire. There were, indeed, significant differences in the uses of the studied past tense forms among the three varieties, which strengthens the idea that there is no linguistic consistency within the different Spanish varieties.…”
Section: Language Variation In Tense and Aspectmentioning
confidence: 94%
“…Even though the examples in (1a-1c) seem to have a straightforward temporal interpretation, as supported by the adverbials used in them, temporality in Spanish has an incredible range of variation in its verbal paradigm; actually, it is in the use of its past tenses that Spanish shows most of its variation. Variation in Spanish TAM is a well-studied phenomenon (Howe, 2006;Schwenter & Cacoullos, 2008;Azpiazu, 2015;González, Jara Yupanqui & Kleinherenbrink, 2019). The Spanish Royal Academies (RAE & ASALE, 2009) points out that, currently, the Present Perfect is the verbal form that shows more geographical variation in its usage, as it seems to be taking over perfective meanings in particular contexts in several Spanish varieties.…”
Section: Language Variation In Tense and Aspectmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the Real Academia Española-the institution that intends to ensure the stability of the Spanish language-points out that the PPC is the verbal form that shows most geographical variation in its usage (NGRAE 2009). Variation in Spanish temporo-aspectual representations has been a well-studied phenomenon and is still a current research focus in variation studies (Howe 2006;Schwenter and Torres Cacoullos 2008;Azpiazu 2013Azpiazu , 2014Azpiazu , 2015González et al 2019;Fuchs 2020;González and Kleinherenbrink 2021;among others).…”
Section: The Use Of the Pretérito Perfecto Compuesto And The Pretérit...mentioning
confidence: 99%
“…In any case, most of this research has been carried out in Peninsular dialects, with specific attention to Central ones, which are spoken by only one tenth of the Spanish speaking population, while constraints on tense-aspect marker variation have been shown to reflect large dialectal differences (e.g., Howe 2006;González et al 2019;Fuchs 2020). A few studies have analyzed the distribution of these forms in Latin American dialects in comparison to their (Central) Peninsular use.…”
Section: The Use Of the Pretérito Perfecto Compuesto And The Pretérit...mentioning
confidence: 99%